EXPERIMENTAL STUDY AND ANALYSIS OF FLAT BELT CONVEYER SYSTEM WITH DIFFERENT WEIGHT CONDITION - Tiwari, Vishnu Dutta; Beohar, Gouraw (International Journal of Research -GRANTHAALAYAH, 2021)
A conveyor belt system essentially consists of an endless belt of elastic material connected between two flat pulleys and driven by the rotation of one of the pulleys by a direct current motor. Usually, the material is fed to the belt near the other end of the pulley. The moving belt that carries the material to the drive pulley tends to sag between the two end pulleys due to its own weight. Rubber conveyor belts are commonly used to transport items with uneven bottom surfaces, small items that fall between rolls, or product bags that sag between rolls.